2020
DOI: 10.1111/jnc.15014
|View full text |Cite
|
Sign up to set email alerts
|

Truncating mutations in SHANK3 associated with global developmental delay interfere with nuclear β‐catenin signaling

Abstract: Mutations in SHANK3, coding for a large scaffold protein of excitatory synapses in the CNS, are associated with neurodevelopmental disorders including autism spectrum disorders and intellectual disability (ID). Several cases have been identified in which the mutation leads to truncation of the protein, eliminating C-terminal sequences required for post-synaptic targeting of the protein. We identify here a patient with a truncating mutation in SHANK3, affected by severe global developmental delay and intellectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 32 publications
6
21
0
Order By: Relevance
“…S1). This is in agreement with recent work where we showed that Shank3 directly binds to β-catenin via its PDZ domain [ 23 ].…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…S1). This is in agreement with recent work where we showed that Shank3 directly binds to β-catenin via its PDZ domain [ 23 ].…”
Section: Resultssupporting
confidence: 94%
“…In contrast, the postsynaptic level of β-catenin is not altered in the postsynaptic density of these Shank3 αβ deficient mice. This is in agreement with our previous work [ 23 ], as interaction of β-catenin with Shank3 is not dependent on the N-terminus of Shank3, but requires the PDZ domain (Fig. 5 c, d).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations